Advances in Dependability Engineering of Complex Systems Proceedings of the Twelfth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2 - 6, 2017, Brunów, Poland (Advances in Intelligent Systems and Computing,, 2018)
This book gathers the proceedings of the 2017 DepCoS-RELCOMEX, an annual conference series that has been organized by the Department of Computer Engineering at the Faculty of Electronics, Wrocław University of Science and Technology, since 2006. Its mission is to continue the heritage of the other two cycles of events - the RELCOMEX conferences (1977-89) and Microcomputer Schools (1985-95) - so this year we can celebrate the 40th anniversary of its origins. In contrast to those preceding series, which were focused on conventional reliability analysis, the goal of DepCoS is to promote a more comprehensive approach to system performability, which is now commonly called dependability. This innovative research area provides answers to the latest challenges in reliability evaluation for contemporary complex systems. Its novelty is based on a multi-disciplinary approach to system theory, technology and maintenance of systems operating in real environments. Dependability analyses concentrate on the efficient completion of tasks, services and jobs by a system considered as a combination of technical, information and human assets, in contrast to "classical" reliability, which is generally limited to the analysis of technical resources and associated components and structures. The selection of papers for this volume illustrates the diversity of topics that need to be considered, from mathematical models and design methodologies through software engineering and data security issues, to practical engineering problems in technical systems. In addition, this edition of the conference hosted the 7th CrISS-DESSERT Workshop, which was devoted to the analysis and assurance of safety and cyber security in critical infrastructure and computer systems.